The Influence of Work Ethic and Work Discipline on the Work Effectiveness of ASN Employees of the Ministry of Defense as Military Reserves at the Headquarters of the Special Forces Command - Bryan Steven; Zulkifli Rangkuti; Nurwulan Kusumadevi (Dinasti Publisher, 2026)
This study aims to analyze and understand in depth the influence of work ethic on employee performance, the influence of work discipline on work effectiveness, and the simultaneous influence of work ethic and work discipline on work effectiveness among ASN employees of the Ministry of Defense assigned as Military Reserves at the Special Forces Command Headquarters. The focus of this research is important considering the demands of professionalism and task accuracy in the defense environment that requires a high level of ethic and discipline. The type of research used is quantitative research, namely research that relies on data in the form of numbers as the basis for statistical analysis. However, this study also utilizes qualitative data as support, in the form of statements, words, or sentences obtained from questionnaires, consultation results, and interviews with related informants. The population in this study amounted to 130 ASN employees, and based on the sampling technique, the researcher used 98 respondents as a sample considered representative to describe field conditions. For hypothesis testing, this study uses the Structural Equation Modeling–Partial Least Square (SEM-PLS) application tool Version 4.0, which is capable of testing relationships between variables comprehensively. The test results show that work ethic (X1) and work discipline (X2) have a positive and significant influence on work effectiveness (Y) partially. In addition, the results of the determination coefficient test (R-Square) of 0.434 or 43.4% indicate that work effectiveness can be explained by these two variables, while the remaining 56.6% is influenced by other factors not included in the scope of the study